Muadalah Policy as a Formal Recognition Solution for Non-Formal Pesantren Education under Law Number 18 of 2019 - Faiqatul Husna; Umlina Mukhlas; Nur Rohim Yunus (Universitas Ibn Khaldun, 2025)
This study examines the implementation of Mu’adalah as a formal recognition system for nonformal pesantren education under Law No. 18 of 2019. Traditionally, pesantren provide religious and moral education through informal methods such as halaqah and classical texts (kitab kuning), without standardized curricula or official certification, limiting graduates’ access to higher education and employment. Using a qualitative-descriptive approach, the research analyzes primary legal documents and secondary academic sources. Findings indicate that Mu’adalah formally equates pesantren diplomas with formal education certificates while maintaining their religious and cultural identity. The policy improves social legitimacy, broadens access to higher education and employment, and integrates traditional education with national standards. Implementation challenges include infrastructure and human resource disparities, resistance from traditionalist pesantren, and regional variations. Overall, Mu’adalah offers an innovative framework that bridges nonformal and formal education, supports inclusive human resource development and educational equity, modernizes pesantrens without compromising their historical and religious essence, and provides valuable guidance for policymakers and administrators. Keywords: Pesantren; Muadalah; Formal recognition of education